Baladni ritem usode - Novak, Boris A. (Jezik in slovstvo, 2011)
The author treats three dimensions of the original, powerful and rich poetics of Svetlana Makarovič. The first topic is the semantic motivation of the traditional ballad meter in the poems written by the contemporary Slovene poet Svetlana Makarovič: she has re-semanticised meter as the stride of Destiny, as an inevitable step of Death. The second topic is the genre nature and the form of her ballads, which do not stem just from the Slovene folk tradition, but fruitfully revive the meta-metrical features of other types of ballads from the wider European and Mediterranean space as well. Through the modernised Slovene ballads of Svetlana Makarovič we can also hear the original danse rhythm of the Italian ballata (and the influence of the Mozarabic zéjel), the circular structure of the medieval French ballade, the dramatic force of the English and Scotish ballads, and the narrative models of the German Volksballade and Kunstballade. The third theme is the phenomenology of Evil: the poet shows the violence committed by the male dominated authoritarian society against those who are weaker, especially children and women. She gives a terrifying insight into the close relation between the lust for power and sexuality.
Keywords: Makarovič, Svetlana, 1939-; Slovenian poetry; slovenska poezija; folk song; balada; ballad; verzologija; Lithuanian Metrica; metrika; meter